Um estudo exploratório envolvendo criptografia e noções de computação quântica - Luiz, Bruna Schwarz Nunes (Universidade Federal de São Carlos, 2021)
In this paper, a proposal for a exploratory study of cryptography and the influence of the quantum computer on data security will be presented. The goal is to demonstrate a way of how factorization and quantum computing can be applied in regular education in the final years of elementary school. Students, despite having a lot of contact with computers on a daily basis, do not understand what a computer is, how safe they are on the social networks and platforms they use, let alone know the development of quantum computing, which is such a current and relevant topic, with a lot of transforming power in everyone's daily life. With the presentation of the classes, students are expected to have an overview of cryptography and quantum computing so that they are thus in contact with mathematics in a more applied and interesting way.
An exploratory study involving cryptography and notions of quantum computing
Keywords: Criptografia; Fatoração; Computador quântico; Estudo exploratório; Encryption; Factorization; Quantum computer; Exploratory study; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA::TEORIA DOS NUMEROS